Effects of preemptive analgesia with celecoxib or acetaminophen on postoperative pain relief following lower extremity orthopedic surgery - Parviz Kashefi (Advanced Biomedical Research, 2012)
Background: Efficacy of preemptive analgesia with nonsteroidal antiinflammatory drugs (NSAIDs) in comparison with acetaminophen is controversial. The present study evaluates the preemptive analgesia efficacy of celecoxib and acetaminophen in comparison with placebo for postoperative pain relief in patients who underwent orthopedic surgery under general anesthesia. Materials and Methods: Ninetypatients eligible for elective distal extremity surgery were categorized in three groups: group C includedpatients who received oral celecoxib 200 mg 2 h before surgery; group A included those who received oral acetaminophen 320 mg 2 h before surgery; and group P included those who received oral placebo 2 h before surgery. Pain scores were recorded at 4, 12, and 24 h after operation. Results: The pain scores 4 h after operation was significantly less in group C than in groups A and P (4.7±1.7 vs. 5±1.5 vs. 6.8±1.7, respectively, P = 0.015). No significant difference was noted in pain scores at 12 h (4.6±2, 4.9±1.9, 4.3±1.4 in group A, group C, group P, respectively P > 0.05) and 24 h (3.1±1.7, 3.0±1.4, 3.3±1.7 in group A, group C, group P, respectively, P > 0.05) after operation among the three groups. Conclusion: Using oral celecoxib 200 mg 2 h before operation is better thanusing oral acetaminophen 320 mg 2 h before the beginning of surgery for control of postoperative pain in patients who underwent lower extremity orthopedic surgery under general anesthesia.